Critical Analysis of Kaumaragara, Kaumaradhara, Kridabhoomi and Kridanaka w.s.r. to NICU, Care Taker, Playground and Toys in Children (AYUSHDHARA, 2024)
Ayurveda, often referred to as the "Science of Life," is a traditional system of medicine that originated in ancient India over 5,000 years ago. It's founded on the principle that health and wellness depend on a delicate balance between the mind, body and spirit. It emphasizes the importance of maintaining this balance for overall well-being. There are different branches of the Ayurvedic science and Kaumarbhritya is one of the eight branches of the system. The word Kaumarbhritya itself denote the importance of nourishment, support and maintenance of child. As a child is the future of great nation. In Ayurveda, Bala Roga encompasses a wide range of considerations and practices. Ensuring the well-being of newborn involves crucial protective rituals. Just as the establishment of a Special Neonatal Intensive Care Unit (SNICU) is pivotal in reducing neonatal mortality rates and enhancing the quality of life for surviving infants. Ayurveda emphasizes the meticulous arrangement of the Sutikagriha (puerperal room) and Kaumaragara (infant care room). This comprehensive approach aims to uphold stringent aseptic conditions and foster a healthy environment for both the mother and the newborn. The significance of toys and play in paediatric care has been overlooked, despite the ancient descriptions by Acharyas outlining the attributes of Kaumaragara (neonatal care unit/paediatric ward), Kaumaradhara (care-givers), Kridabhoomi (playground) and Kridanaka (toys). These elements are regarded as foundational to nurturing a thriving and flourishing individual.